2022
DOI: 10.1109/access.2022.3218410
|View full text |Cite
|
Sign up to set email alerts
|

Semantics- and Task-Oriented Scheduling for Networked Control Systems in Practice

Abstract: Networked control systems (NCSs) are feedback control loops closed over a communication network. Emerging applications, such as telerobotics, drones, and autonomous driving, are the most prominent examples of such systems. Regular and timely information sharing between the components of NCSs is essential to fulfilling the desired control tasks, as stale information can lead to performance degradation or even physical damage. In this work, we consider multiple heterogeneous NCSs that transmit their system state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…One of the possible extensions of this work would be the implementation of the FH scheduling algorithm on real hardware, e.g., using software-defined radios as in [47]. Moreover, the proposed theoretical framework can be employed to capture alternative task-criticalities, contexts, and semantics through the replacement of the utilized scheduling metric, i.e., nMSE, with a different age-penalty function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible extensions of this work would be the implementation of the FH scheduling algorithm on real hardware, e.g., using software-defined radios as in [47]. Moreover, the proposed theoretical framework can be employed to capture alternative task-criticalities, contexts, and semantics through the replacement of the utilized scheduling metric, i.e., nMSE, with a different age-penalty function.…”
Section: Discussionmentioning
confidence: 99%
“…To name an example, in a different work involving real-life measurements, we have shown that simple contention-free protocols outperform the random access protocols mentioned above w.r.t. information freshness and control performance [47]. Therefore, we do not consider contention-based protocols in the remainder of this work.…”
Section: Greedy Uplink and Downlink Schedulingmentioning
confidence: 99%
“…the paper [48] discusses the potential energy savings resulting from semantic interaction in connected autonomous vehicles; and the paper [49] demonstrates the effectiveness of semantics powered sampling for remote real-time source reconstruction. We refer the interested reader to [50], [51], and the references therein for additional details. In this work, we capture the semantics of information using the value of information (VoI) metric [26].…”
Section: ) Semantic Communicationmentioning
confidence: 99%
“…The sampling periodicity is set to 10 ms. The selection of the parameters defines the state-space representation (1) of IP, the details of which can be found in [9]. III.…”
Section: Introductionmentioning
confidence: 99%